Fecal Microbiota Transplantation: A Systematic Review of Therapeutic Potential, Preparation Techniques, and Delivery Methods Across Medical Conditions - Qadir , Syamand Ahmed; ALKaisy , Qausar Hamed; F. Hasan, Abdulbasit; Awlqadr, Farhang Hameed; Altemimi, Ammar B.; Faraj , Aryan Mahmood; Giuffrè , Angelo Maria; N. Saeed, Mohammed; Abdalla , Sherzad Rasul (Kurdistan Journal of Applied Research, 2024)
Fecal microbiota transplantation (FMT) is revolutionizing the treatment of gastrointestinal disorders by leveraging the gut microbiome in innovative ways. This systematic review evaluates the clinical effectiveness and safety of FMT across various medical conditions, offering insights into its therapeutic potential and limitations. A comprehensive search of PubMed, Web of Science, Scopus, Embase, and ClinicalTrials.gov from January 2000 to December 2023 identified 97 relevant studies on FMT’s efficacy, safety, and microbiome changes after eliminating duplicates. FMT has demonstrated high success rates, particularly in treating recurrent and refractory Clostridium difficile infections (CDI), with up to 90% effectiveness, establishing it as a primary treatment for antibiotic-resistant cases. FMT’s applications are expanding to inflammatory bowel diseases (IBD), including ulcerative colitis and Crohn’s disease, as well as metabolic disorders and neuropsychiatric conditions. Remission rates for IBD range from 37-45%, with outcomes influenced by donor characteristics, stool preparation, and disease subtype. with mild, self-limiting side effects such as transient diarrhea and abdominal cramping. However, rare serious adverse events underscore the need for rigorous donor screening and standardized preparation protocols to mitigate risks. FMT’s ability to restore healthy gut flora highlights its promise in both gastrointestinal and systemic disease management. However, further research is essential to establish optimized procedures, standardized guidelines, and long-term safety data to facilitate its integration into mainstream medical practice.